THE EXISTENCE OF ADAT LAND POST-ENACTMENT OF LAW NUMBER 6 OF 2014 ON VILLAGE - Sri Hajati; Oemar Mochthar; Sri Winarsi (Jurnal Dinamika Hukum, 2016)
Post-Enactment of Law No. 6 Year 2014 on village, a village is divided into two: villages and adat villages. Adat village may have adat land assets. The law will not be explained in more detail, in addition to the Regulation of the State Minister of Agrarian/Head of National Land Agency No. 5 Year 1999 which was repealed in 2015 resulting in a legal vacuum in the regulation of traditional dispute resolution. This research apllied statute and conceptual approach while the analysis was conducted qualitatively, by pointing to the principles and procedural law as well as analyzing the various factors of social, economic and political process and procedural subtantive resolution of cases. The causal factors do not explain the existence of adat land which is not accommodated by local regulations as an obligation for local governments to undertake research and data collection ulayat lands in their area, as mandated by Law No. 23 Year 2014 which was confirmed by Regulation No. 38 of 2007 and Law No. 6 Year 2014.Keywords: Village Government, Ulayat Land Rights, Society